2017
DOI: 10.3389/fphar.2017.00624
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Endogenous Hydrogen Sulfide and Homocysteine in Chronic Obstructive Pulmonary Disease Combined with Cardiovascular Disease

Abstract: Background: Considerable studies showed associations between chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD), we evaluated the role of endogenous hydrogen sulfide (H2S)/homocysteine (Hcy) in patients with COPD combined with CVD.Methods: Fifty one stable patients with COPD were enrolled (25 COPD, 26 COPD + CVD). Lung function, sputum, peripheral blood samples, serum H2S, Hcy, high-sensitivity C-reactive protein (hs-CRP) and tumor necrosis factor-α (TNF-α) levels were measured. Dysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
2
8
0
2
Order By: Relevance
“…13 Reduced production of endogenous H 2 S during hyperhomocysteinemia has emerged as one of the causes of hypertension and vascular disease. 31 Our research also found that high concentrations of Hcy reduced endogenous H 2 S levels in vascular endothelial cells by reducing the expression of CBS and CSE. At the same time, lower expression CBS and CSE also cause Hcy metabolic disorders, which are accumulated in the body and damage the vascular endothelium.…”
Section: Discussionsupporting
confidence: 68%
“…13 Reduced production of endogenous H 2 S during hyperhomocysteinemia has emerged as one of the causes of hypertension and vascular disease. 31 Our research also found that high concentrations of Hcy reduced endogenous H 2 S levels in vascular endothelial cells by reducing the expression of CBS and CSE. At the same time, lower expression CBS and CSE also cause Hcy metabolic disorders, which are accumulated in the body and damage the vascular endothelium.…”
Section: Discussionsupporting
confidence: 68%
“…Accumulating evidence supports the inhibitory effect of HCy on H 2 S generation [ 83 , 84 , 85 ], but there were also reports of elevated H 2 S levels in HHCy [ 86 , 87 ]. The evidence of defective and enhanced H 2 S production under HHCy conditions and the metabolic imbalance of HCy and H 2 S in cardiovascular pathologies suggests that changes in the H 2 S/HCy ratio may be more valuable than changes in the absolute concentrations of H 2 S and HCy in depicting the role of these metabolites in disease pathogenesis [ 88 , 89 , 90 ]. There are growing controversies on the physiologically significant concentrations of H 2 S and its biological effects [ 91 , 92 ].…”
Section: H 2 S As a Gasotransmittermentioning
confidence: 99%
“…It has been reported that increased expression of Hcy can accelerate the development of the disease by causing damage to vascular endothelial cells [6]. More and more evidences have shown that elevated plasma Hcy levels may also contribute to poor prognosis of COPD patients [7][8][9]. In addition, studies have indicated that other methods of reducing total Hcy level may yield different results on serum inflammatory markers [3].…”
Section: Introductionmentioning
confidence: 99%